Perancangan Interior Makerspace dan Gallery Café “The Workshop” di Surabaya - Vienna Ernes Fellisia Setiawan; Cok Gede Padmanaba; Sherly de Yong (Intra, 2016)
Abstrac—Skills are needed as individual to develop themselves. Skills also became a major to starting a business. Learning a skill is now becoming a lifestyle in the society especially in big cities, such as Surabaya. There are many kinds of skills, depending on the specialization of each individual. Sometimes people get trouble to finding a workshop that they interesting in, so it needs attention tofulfill the requirement of society. The method that designer used is the method of design thinking. The Results of the design is not just become a means of exhibitions, but also become a means to increase the knowledge for people with specialization in vocational training.